La estética de la Guerra del Pacífico en el teatro patriótico chileno - Donoso Rojas, Carlos; Huidobro Salazar, María (Latin American Theatre Review, 2016)
Historically, theatre has served as a cultural and aesthetic resource for the promotion of ideas, discourses and symbols, as well as for the production and promotion of feelings. In the context of war, the scenic arts can serve to socially and culturally legitimize a national cause through the aesthetic, exemplary representation of opposing sides. In Chile, the War of the Pacific (1879-1883) made possible the development of a theatre that looked to incorporate the masses in the understanding and assimilation of the conflict. This was achieved through simple but effective stagings, where the archetypal construction of the enemy was transformed into an essential means of self-definition, self-balancing, and the legitimization of the appropriate cause.